(untitled) (Bangladesh Pharmaceutical Journal, 2019)
Grewia asiatica (Family-Malvaceae), known as Phalsa in Bangladesh, is also native to India, Nepal, Pakistan, Cambodia and Thailand. The plant has a long history of traditional uses. The present investigation was designed to evaluate acute toxicity test, antidepressant and sedative-hypnotic activities of the methanolic extract of the leaves of G. asiatica. In acute toxicity test, methanolic soluble fraction of the plant extract of G. asiatica showed no significant changes in the body weight between the control and treated group at the doses of 1000, 2000 and 3000 mg/kg body weight. The extract could not significantly reduce immobility time in comparison with control group and standard drug (Nortriptyline) treated group in forced swimming and tail suspension tests. Sedative-hypnotic activity was evident at the doses of 100 and 200 mg/kg body weight after observing in hole board test. Sedative-hypnotic activity of short duration of action was also evident in hole cross and open field test. Bangladesh Pharmaceutical Journal 22(2): 185-191, 2019